Answer:
-37
Step-by-step explanation:
for the first equation to equal 4 the x must equal -6.
because something plus 7 had to equal 4. and we know that -3 + 7 equals 4. Now, -6 ÷ 2 equals -3 and that gives us the right answer.
So now plug -6 into the new problem so now it is
5 × (-6) - 7 so according the PEMDAS, we do 5 × -6 first which is -30. and -30 - 7 equals -37!!
hope this helps :)
Answer:
the first one
Step-by-step explanation:
Answer:
x = 1 and y = 2
Step-by-step explanation:
Let apples are represented by x
and let oranges are represented by y
You purchase 5 pounds of apples and 2 pounds of oranges for $9. This line in equation format can be written as:
5x + 2y = 9
Your friend purchases 5 pounds of apples and 6 pounds of oranges for $17.
This line in equation format can be written as:
5x + 6y = 17
Now we have two equations:
5x + 2y = 9 -> eq (i)
5x + 6y = 17 -> eq(ii)
We can solve these equations to find the value of x and y.
Subtracting eq(i) from eq(ii)
5x + 6y = 17
5x + 2y = 9
- - -
_________
0+4y= 8
=> 4y = 8
y= 8/4
y = 2
Now, putting value of y in eq (i)
5x + 2y = 9
5x +2(2) = 9
5x +4 = 9
5x = 9-4
5x = 5
x = 1
so, x = 1 and y = 2
Answer:
y=0.5x+3
Step-by-step explanation:
Answer:
![f(x)=x+5](https://tex.z-dn.net/?f=f%28x%29%3Dx%2B5)
Step-by-step explanation:
The rate of change (slope) is 1 which is more than function 2 and less than function 1